A construcionalização e a rede construcional de [ir/vir + INFINITIVO] em português brasileiro: uma análise baseada no uso - Oréfice, Patrícia [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
O objetivo deste trabalho é discutir as construções formadas pelos verbos ir/vir seguidos de infinitivo, relacionando-as à construção prototípica de finalidade, a oração adverbial final, demonstrando a rede construcional (TRAUGOTT; TROUSDALE, 2013) formada por essas construções. Mais especificamente os objetivos deste trabalho são a CMCP (Construção de Movimento com Propósito), formada por dois verbos, onde V1 é um verbo de movimento orientado e V2 é um verbo em forma infinitiva (ORÉFICE, 2014), CPP (Construção Perifrástica de Passado), cuja semântica indica um deslocamento temporal ao momento anterior à fala, e CFV2 (Construção Focalizadora da Ação), a qual indica focalização da ação verbal expressa pela construção, dando ênfase à ação de V2. Esta tese, embasada nos pressupostos teóricos do Modelo Baseado no Uso, por meio do processo de construcionalização (TRAUGOTT; TROUSDALE, 2013), apresenta a hipótese de uma rede construcional das construções supracitadas, relacionando-as, de forma hierárquica, às construções de finalidade prototípicas (adverbial final). Nossas análises, feitas de forma qualitativa e quantitativa, são embasadas em dados de fala, coletados no Corpus do Projeto Iboruna.

The goal of this work is to discuss the constructions formed by the verbs ir/vir (to go/to come) followed by infinitive, in its relationship with the prototypical construction of purpose, final adverbial clause, showing the constructional network (TRAUGOTT; TROUSDALE, 2013) formed by this constructions. More specifically the goals of this work are CMCP (Construction Motion Cum Purpose), formed by two verbs, where V1 is a oriented motion verb and V2 is a verb in the infinitive form (ORÉFICE, 2014), CPP (Past Paraphrastic Construction), whose semantics indicates a temporal displacement to the moment before the speech, and CFV2 (Action Focused Construction), which indicates focalization of the verbal action expressed by construction, emphasizing the V2 action. This thesis, supported by theoretical assumptions of Usage-Based Linguistics, by means of the process of construcionalization (TRAUGOTT; TROUSDALE, 2013), presents the hypothesis of a construcional network of the constructions mentioned, relating then by hierarchical form with the prototypical purpose constructions (purpose clause). Our analysis, made in qualitative and quantitative way, are supported in spoken data, collected in the corpus of Iboruna Project.
Constructionalization and constructional network of [ir/vir + INFINITIVE] in brazilian portuguese: an analyze based in use.
Keywords: Construcionalização; Construção; Modelo Baseado no Uso; Finalidade; Verbo ir; Verbo vir; Construcionalization; Construction; Usage-Based Linguistics; Verb ir; Verb vir